Unveiling The Hidden Gems: Exploring The Colonial Context In Indian Novels Of The Nineteenth Century (Journal of Namibian Studies : History Politics Culture, 2023)
This paper offers a deep analysis of the colonial backdrop in Indian novels from the 1800s, shedding light on a literary period that is often disregarded in favor of the more widely acknowledged post-colonial literature. In the course of our investigation, we shed light on the often overlooked aspects of colonial literature, revealing a fresh perspective on the profound ideas, artistic methods, and societal significance they embody. The paper explores the lasting impact of British colonial rule on the Indian mindset as seen in literature, while also highlighting the complex relationship between colonial power dynamics and indigenous culture. Through a careful examination of noteworthy literary pieces and their respective creators, it becomes evident that these novels possess the ability to challenge the prevailing colonial narrative. Moreover, they effectively capture the intricate cultural, social, and psychological shifts that occurred during this particular era. The study thus highlights the importance of these novels in comprehending the intricacies of India's colonial history and its lasting impact on present-day Indian literature and society.